Phosphazene-Catalyzed Regioselective Condensation of Allyl Thioethers with Aldehydes: A Rapid Approach to 1,3-Dienyl Sulfides, -Sulfoxides and -Sulfones - Phae-nok, Supasorn; Kuhakarn, Chutima; Leowanawat, Pawaret; Reutrakul, Vichai; Soorukram, Darunee (Synthesis, 2024)
The phosphazene-catalyzed regioselective condensation of allyl thioethers with aldehydes is investigated. Upon treatment of allyl thioethers with P4-t-Bu, allyl thioether anions are generated and rapidly react with aromatic aldehydes, leading to 1,3-dienyl sulfides in good yields with high regioselectivity. This finding provides an alternative approach for the preparation of allyl thioether anions in a regioselective manner. In addition, chemoselective transformations of 1,3-dienyl sulfides to provide the corresponding 1,3-dienyl sulfoxides or 1,3-dienyl sulfones are also demonstrated.
Keywords: 1,3-dienyl sulfides; 1,3-dienyl sulfones; 1,3-dienyl sulfoxides; phosphazene; allyl thioethers; allyl sulfides; organosulfur